Comparison of case-based learning and traditional lecture in teaching residents on research misconduct: a controlled before-and-after study - Chen, Lulin; Li, Yizhao; Guo, Xiaoyan; Liu, Wei (PloS one, 2025)
As scientific outputs continue to surge, research misconduct has garnered global attention. Case-based learning (CBL), an active student-centered learning strategy, possesses many advantages but has not been widely used in China due to resource constraints. This study aimed to address the research gap regarding the impact of CBL and traditional lecture on residents’ knowledge and attitudes towards research misconduct. This controlled before-and-after study was conducted at two tertiary hospitals in southwest China from November 2022 through March 2023. All medical residents at the two hospitals were defined as participants. Residents participating in CBL course at one hospital comprised the experimental group, whereas those engaging in traditional lecture at another hospital constituted the control group. The CBL and control group included 202 and 205 individuals, respectively. A total of 298 subjects were successfully matched after propensity score matching, with 149 individuals in each group. After the courses, the participants’ knowledge on research misconduct, perceived consequences for research misconduct, and their agreement rate regarding research misconduct improved in the CBL and control group ( P < 0.05), but certain aspects of their perceived consequences and agreement rate did not show significant improvement in the control group. The results revealed that there is a marked enhancement in residents’ knowledge about research misconduct, their perception of its consequences, and their overall disapproval of such behavior in the CBL group. This underscores the effectiveness of CBL in fostering a deeper understanding and stronger aversion towards research misconduct among residents.